1976
DOI: 10.2172/7123189
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature lithium/sulfur secondary battery. Annual progress report, December 1, 1974--December 1, 1975. [Ambient-temperature battery with dissolved S]

Abstract: The purpose of this program is to develop an ambient temperature Li/S secondary battery. The proposed configuration is Li/Organic Electrolyte, Dissolved S/catalytic electrode or current collector In a typical practical arrangement, this battery will have an energy density of 100 Whr/lb, including the weight of cell hardware, if a 5M S solution is discharged with 50% efficiency at 2.0V. Investigations of S solubility and electrochemistry have been undertaken in polar, aprotic nonaqueous solvents, chosen for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…There is good agreement between the experimental results and those calculated from numbers based on the above overall mechanisms (Eq. [6], [7]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is good agreement between the experimental results and those calculated from numbers based on the above overall mechanisms (Eq. [6], [7]).…”
Section: Resultsmentioning
confidence: 99%
“…This has been attributed to blockage of the cathode by reaction products and to slow reduction kinetics of low order polysulfides (PS), the latter being solvent dependent (5). Studies of the redox behavior of sulfur and PS in various aprotic solvents showed the overall reaction to be a multielectron process with many equilibrium reactions between sulfur and PS (6,7). It was further found that reduction of low order PS was more pronounced in THF than in DMSO (8).…”
mentioning
confidence: 99%
“…There is considerable interest in rechargeable lithium–sulfur batteries because their theoretical specific energy, 2600 Wh/kg, is 5 times greater than that of current lithium-ion batteries. Elemental sulfur is abundant, nontoxic, and inexpensive compared to cobalt- and iron-based cathodes in conventional lithium-ion batteries . There are, however, many challenges that must be addressed before lithium–sulfur batteries become a commercial reality .…”
Section: Introductionmentioning
confidence: 99%
“…Until this point we have provided no insight on the distribution of values of x present in the system. UV–vis spectroscopy has been used to distinguish the Li 2 S x speciation in organic solvents such as DMSO, , DMF, THF, ,,,, dimethylacetamide, liquid ammonia, , and acetonitrile . Detailed spectroelectrochemical experiments are necessary for unambiguous determination of speciation. ,,, These studies show that the distributions of species present depend crucially on the solvent.…”
Section: Resultsmentioning
confidence: 99%